Virus infections in children with acute lymphoblastic leukaemia. Issue 10 (October 1979) - Craft, A W; Reid, M M; Gardner, P S; Jackson, E; Kernahan, J; McQuillin, J; Noble, T C; Walker, W
Abstract : The pattern of virus isolation and illness was studied in 64 children with acute lymphoblastic leukaemia (ALL) during periods of apparent infection and when the children were well. The virus isolation rate of 2.2 viruses per child a year is similar to that previously found in normal children. In only 32% of children with symptoms were viruses found and 14.5% had viruses isolated when asymptomatic. The children with ALL appear to be more vulnerable to multiple virus infections and to excrete the virus for longer periods. This may be due to failure of production of both local and systemic antibodies. The failure in the past to recognise the true importance of virus infections in ALL may have been due to inadequate diagnostic techniques.